Frequency of IL-1B Gene Polymorphisms in Patients with Gastroesophageal Cancer in the Hakkari Region - Derya Yaman; Selin Akad-Dinçer; Yusuf Karakaş; Gözde Ünsoy; Yunus Kasım Terzi; Feride İffet Şahin (Gazi Medical Journal)
Objective: Gastric cancer is a complex malignant tumor associated with chronic inflammation. In the present study, we aimed to investigate the frequency of interleukin 1B (IL-1B) gene polymorphisms affecting gene expression in patients with gastroesophageal cancer (GC) diagnosed in the Hakkari region. Methods: Blood samples of 17 patients with GC (group 1) and 59 healthy controls (group 2) were enrolled in the study. The single-nucleotide polymorphisms (SNPs) rs1143627 c.-118C>T, rs16944 c.-598C>T, and rs1143634 c.315C>T polymorphisms in the IL-1B gene were studied among groups via polymerase chain reaction and restriction fragment length polymorphism. Results were analyzed by descriptive statistics and the x2 test. The association between SNPs and GC risk was evaluated by odd ratios (ORs) and 95% confidence intervals. Results: The frequencies of the three genotypes in the SNP rs1143627, rs16944, and rs1143634 were similar between the groups, and C>T transition was not found to be significant [(p=0.69, OR: 1.16 95%, confidence interval (CI): 0.54-2.51; p= 0.16, OR: 0.58 95%, CI: 0.26- 1.25; p=0.7, OR: 0.83 95%, CI: 0.32-2.11, respectively]. Conclusion: Our results did not reveal any significant association between IL-1B gene SNPs and gastroesophageal cancer in the Hakkari region.